Acute kidney injury after transcatheter aortic valve replacement in the elderly: outcomes and risk management - Zaleska-Kociecka M (Dove Medical Press, 2019)
Marta Zaleska-Kociecka,1 Maciej Dabrowski,2 Janina Stepinska1 1Cardiac Intensive Therapy Clinic, Institute of Cardiology, Warsaw, Poland; 2Interventional Cardiology and Angiology Clinic, Institute of Cardiology, Warsaw, Poland Abstract: Aortic stenosis is the most common cause of valve replacement in Europe and North America with prevalence increasing with age. Transcatheter valve replacement (TAVR) represents an alternative for surgical valve replacement of severely stenotic valves. Despite lower risk of acute kidney injury compared to that associated with surgery, this complication remains prevalent in patients undergoing TAVR. There is a paucity of data confirming the relation of acute kidney injury with high morbidity and mortality, especially when superimposed on chronic kidney disease, which is a frequent comorbidity in the elderly with severe aortic stenosis. As there is no consensus on the prevention of acute kidney injury in patients undergoing TAVR, identification and limitation of risk factors are crucial. In this review, we aim to discuss the key aspects of acute kidney injury diagnosis, risk assessment, and outcomes in TAVR patients, and to point out gaps in current knowledge. Keywords: acute kidney injury, TAVI, transcatheter valve replacement, valvular disease, aortic stenosis, aortic valve replacement